2023
DOI: 10.3390/tropicalmed8070373
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Toxicity during the Treatment of Latent Tuberculous Infection in a Referral Center in Spain

Abstract: The screening and treatment of latent tuberculosis infection (LTBI) in countries with a low incidence of TB is a key strategy for the elimination of tuberculosis (TB). However, treatment can result in adverse events (AEs) and have poor adherence. This study aimed to describe treatment outcomes and AEs for LTBI patients at two departments in Vall d’Hebron University Hospital in Barcelona, Spain. A retrospective study was conducted on all persons treated for LTBI between January 2018 and December 2020. Variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…The percentages of TB preventive treatment non-adherence among adult contacts of pulmonary TB cases found in Catalonia, Spain, in this study were similar or higher than those found in studies carried out in Spain [ 15 , 16 , 17 , 18 ]. In a study carried out in the province of Lleida in 2016, a non-adherence rate of 29.7% was found in a cohort of 199 contacts (with an average age of 45.1 years) [ 16 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The percentages of TB preventive treatment non-adherence among adult contacts of pulmonary TB cases found in Catalonia, Spain, in this study were similar or higher than those found in studies carried out in Spain [ 15 , 16 , 17 , 18 ]. In a study carried out in the province of Lleida in 2016, a non-adherence rate of 29.7% was found in a cohort of 199 contacts (with an average age of 45.1 years) [ 16 ].…”
Section: Discussionsupporting
confidence: 81%
“…In a study carried out in the province of Alicante in 2011, a non-adherence percentage of 19.6% was found in a cohort of 338 contacts (average age of 34.1 years) [ 17 ]. In a study carried out in the city of Barcelona by the Vall d’Hebron Hospital in 2018–2020, a non-adherence percentage of 13.4% (95% CI: 9.1–17.7%) was found among 261 (24.1%) contacts [ 18 ]. Nevertheless, it is difficult to compare non-adherence rates observed in different studies due to their different methodologies and settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation